Strong nonlinear optics in on-chip coupled lithium niobate microdisk photonic molecules. (21st July 2020) - Wang, Min; Yao, Ni; Wu, Rongbo; Fang, Zhiwei; Lv, Shilong; Zhang, Jianhao; Lin, Jintian; Fang, Wei; Cheng, Ya
Abstract: High-quality lithium niobate (LN) thin-film microresonators provide an ideal platform for on-chip nonlinear optical applications. The strict phase-matching condition should be satisfied for an efficient nonlinear optical process, which requires dispersion engineering with an LN microresonator. However, this is challenging in single microresonator, resulting from the fabrication error. Here, we demonstrate strong nonlinear effects in a photonic molecule (PM) structure composed of two strongly coupled lithium niobate microdisks. The size mismatch of the microdisks enables phase matching by employing coupling-induced frequency splitting to compensate for the material and geometric dispersion. With a continuous wave excitation, rich nonlinear optical phenomena including cascaded four-wave mixing and stimulated Raman scattering were observed around the second harmonic signal. Meanwhile, an ultra-high four-wave mixing absolute conversion efficiency of 14% as obtained when the second harmonic signal power is at microwatts level. The LN PM is of great potential for applications in nonlinear integrated photonics.